(untitled) - Christensen, Stig Moller (Copenhagen, Denmark, 2003)
The four main scientific objects in this dissertation are: document and analyse the interactions, interdependencies, and conflicts between the local community dependent on natural resource within buffer and conservation zones of Damdoi forest enterprise,...
Keywords: Natural resources,Conservation of natural resources; Mekong delta,vietnam